Dosimetry for therapeutic treatment of neuroblastoma by 131I-mIBG - Sudbrock, F.; Eschner, W.; Schmidt, M.; Simon, T.; Hero, B.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2006)
Aim: Targeted radiotherapies using iodine-131 meta-iodobenzylguanidin have long been in use for treatment of stage IV neuroblastoma but reliable dosimetric data are scarce. Method: This work presents an approach to determine the whole body exposure and tumour doses delivered during therapy. Dosimetric data are reported and discussed for six treatments carried out according to the trial protocol NB2004 as it is in use in our study in the last two years. Results: Whole body exposures are found to be in the range of 1.75 to 2.5 Gy whereas tumour doses vary between 15 and 55 Gy. Conclusion: The course of action prescribed by the trial protocol allows whole body exposure as well as tumour doses to be determined routinely.
Keywords: Neuroblastom; mIBG-Therapie; Ganzkörperszintigraphie; SPECT; Dosimetrie; Energiedosis